Some variables affecting the characteristics of Eudragit E-sodium alginate polyelectrolyte complex as a tablet matrix for diltiazem hydrochloride - Yusif Rehab Mohammad; Hashim Irhan Ibrahim Abu; El-Dahan Marwa Salah (Acta Pharmaceutica)
Eudragit E (EE)-sodium alginate (SA) polyelectrolyte complexes (PECs) were prepared at pH 4 and 5.8 using sodium alginate of high (SAH) and low viscosity (SAL). The optimum EE-SA complexation mass ratio was determined using viscosity measurements. Interactions between EE and SA in PECs were characterized by Fourier transform infra-red spectroscopy (FT-IR) and differential scanning calorimetry (DSC). Diltiazem hydrochloride (DTZ HCl) tablets were prepared using the prepared EE-SA PECs and their physical mixtures at different ratios as matrices. Tablets were evaluated for swelling characteristics and in vitro drug release. Tablets containing EE-SAH physical mixtures of ratios (1.5:1 and 1:3) as matrices were effective in achieving sustained release of DTZ HCl, where the percent drug released was significantly (p < 0.05) decreased compared to that from tablets either containing the same ratios of EE-SAL physical mixtures or the preformed EE- -SAH and EE-SAL PECs.